(untitled) (London Journal of Engineering Research, 2024)
An evaluation of the risks influencing project performance was conducted in the railway construction industry in the Eastern area of Nigeria in order to reduce the risks connected with a specific activity and the potential for worker harm. The data obtained from a self-administered questionnaire survey of the construction industries was calculated using the Likert scale and the mean index formula following a brief instruction on health, safety, and environmental culture in the industry. Using a qualitative approach to data analysis and a matrix analysis table, the amount of risk was ascertained. Six categories of hazards, together with their subcategories, were chosen from construction-related projects based on the literature that was mentioned. To ensure that every company in the research region was equally represented, three firms were chosen at random from each state. Employees in the chosen construction industry received 160 questionnaires in total. 44 did not answer for a variety of reasons, bringing the sample size down to 116. A rate of 72.5% for the respondent was found. Within two months, the distribution and collection were completed. Using Cronbach’s alpha reliability coefficient, which gauges the consistency of elements in question answers, reliability tests were run on each risk scale. Social, political, and construction hazards are the riskiest of the six categories of risk mentioned. The findings are consistent with the literature, which shows that the most common dangers in the construction sectors within the analyzed locations are poor safety performance and a lack of understanding of safety regulations